A case report of heterotopic pregnancy - R., Keerathana; S., Sundar Narayanan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Heterotopic pregnancy is the presence of both intrauterine and extrauterine (ectopic) implantation as described by Reece in 1983 and is extremely rare. It accounts for 1 per 30000, in natural cycles and 9 per 10000, in assisted reproduction cycles. The aim of this report is to introduce this case as it poses a challenge to diagnosis due to its complex clinical and laboratory findings. A primigravida aged 30 at 6 weeks period of gestation, reported with minimal bleeding per vaginum. On performing a physical examination her vitals were stable and no significant findings were noted except for an enlarged uterus corresponding to 6 weeks with posterior forniceal fullness. Her beta-hCG was 23765 IU/ml and ultrasound showed a live intrauterine gestation with left adnexal mass- likely ectopic gestational sac. Laparoscopy showed a left tubal pregnancy and salpingectomy was done. The postoperative period was uneventful and she was discharged with a single live intrauterine gestation of 6-7 weeks. She carried on with her pregnancy and delivered a healthy baby at term. The diagnosis is possible only in cases when there is a high index of suspicion by the treating clinician. The adnexa must be inspected carefully in the confirmatory ultrasound. The early timely diagnosis gives a good maternal outcome and hence crucial in the management.